2020
DOI: 10.1371/journal.pone.0238179
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression profiling of the carotenoid cleavage dioxygenase (CCD) gene family in Brassica napus L

Abstract: Carotenoid cleavage dioxygenase (CCD), a key enzyme in carotenoid metabolism, cleaves carotenoids to form apo-carotenoids, which play a major role in plant growth and stress responses. CCD genes had not previously been systematically characterized in Brassica napus (rapeseed), an important oil crop worldwide. In this study, we identified 30 BnCCD genes and classified them into nine subgroups based on a phylogenetic analysis. We identified the chromosomal locations, gene structures, and cis-promoter elements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…Among the identified CBP, XBP, and ABP genes, none of these genes have a transmembrane region. Similar results were obtained in higher plants, such as Musa acuminata [ 64 ], Brassica napus [ 65 ], N. officinale (unpublished data), Triticum aestivum [ 24 ], and green algae Tetraselmis suecica [ 21 ], which do not possess any transmembrane regions in their CBP genes.…”
Section: Resultssupporting
confidence: 73%
“…Among the identified CBP, XBP, and ABP genes, none of these genes have a transmembrane region. Similar results were obtained in higher plants, such as Musa acuminata [ 64 ], Brassica napus [ 65 ], N. officinale (unpublished data), Triticum aestivum [ 24 ], and green algae Tetraselmis suecica [ 21 ], which do not possess any transmembrane regions in their CBP genes.…”
Section: Resultssupporting
confidence: 73%
“…majus . Similarly, some CBP genes in the higher plants such as Banana ( MaPSY1 and MaPSY3 ), wheat ( TaPSY3 ), and Brassica napus ( BnCCD ) also do not possess any transmembrane region. Homology analysis using CDD showed that the CBP amino acid sequences had high similarity with other higher plant species, including the sequences of amino acids 66–407 for NoPSY , 4–564 for NoPDS , 1–137 for NoCrtISO , 56–501 for NoLCYB , 1–526 for NoLCYE , 1–303 for NoCHXB , 1–249 for NoZEP , 1–170 for NoCCD , 5–527 for NoNCED , 34–225 for NoCHXE-p , and 11–318 for NoZDS-p . In green algae, Dunaliella salina homology analysis of CBP genes by CCD showed high homology with other microalgae and higher plants. ,, From these results, it can be inferred that N.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In the present study, 10, 9, 9, 13, 8, and 8 CCDs protein sequences were identified in watermelon, melon, cucumber, pumpkin, bottle gourd, and wax gourd, respectively ( Table 1 ). A total of 30, 19, 7, and 11 CCDs protein sequences were identified in oilseed rape [ 34 ], tobacco [ 1 ], tomato [ 11 ], and pepper [ 12 ], respectively. Molecular characteristics of all CCDs protein members of Cucurbitaceae are different, and proteins in the same clade showed different molecular weights and isoelectric points.…”
Section: Discussionmentioning
confidence: 99%
“…The CCD gene family is an ancient gene family in plants that plays a vital role in plant growth and stress response [ 34 ]. CCDs proteins are implicated in the production of various hormones and aromatic substances in plants [ 37 ].…”
Section: Discussionmentioning
confidence: 99%